2009
DOI: 10.1002/chem.200801807
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump for O2 Reduction Catalyzed by 5,10,15,20‐Tetraphenylporphyrinatocobalt(II)

Abstract: Oxygen reduction: A polarized water|1,2‐dichloroethane (DCE) interface acts as a proton pump for the [Co(tpp)] (TPP=5,10,15,20‐tetraphenylporphyrinato) catalyzed O2 reduction by ferrocene (Fc) compounds to produce H2O2 (see figure; IT=ion transfer, ET=electron transfer). This system favours the collection of H2O2 by extraction immediately after its formation in DCE to the adjacent water phase.magnified imageThe role of 5,10,15,20‐tetraphenylporphyrinatocobalt(II) ([Co(tpp)]) as a catalyst on molecular oxygen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 34 publications
(41 reference statements)
7
71
0
Order By: Relevance
“…Bis(triphenylphosphoranylidene)ammonium tetrakis(pentafluorophenyl)borate (BATB) was prepared by metathesis of bis(triphenylphosphoranylidene)ammonium chloride (Sigma-Aldrich) and lithium tetrakis(pentafluorophenyl)borate (LiTB) (ABCR) following the procedure described earlier [19] and recrystallized twice from acetone. 1,2-Dichloroethane (DCE, N99%+), and HClO 4 (70%) were obtained from Sigma-Aldrich.…”
Section: Chemicalsmentioning
confidence: 99%
“…Bis(triphenylphosphoranylidene)ammonium tetrakis(pentafluorophenyl)borate (BATB) was prepared by metathesis of bis(triphenylphosphoranylidene)ammonium chloride (Sigma-Aldrich) and lithium tetrakis(pentafluorophenyl)borate (LiTB) (ABCR) following the procedure described earlier [19] and recrystallized twice from acetone. 1,2-Dichloroethane (DCE, N99%+), and HClO 4 (70%) were obtained from Sigma-Aldrich.…”
Section: Chemicalsmentioning
confidence: 99%
“…In the case of DMFc, it has been shown that oxygen reduction at the polarized water/DCE interface produces decamethylferrocenium (DMFc + ) and hydrogen peroxide (H 2 O 2 ), on the basis of two-phase reactions [7] and in situ detection of H 2 O 2 using scanning electrochemical microscopy [13]. The catalytic effect of various porphyrin compounds, such as cobalt tetraphenylporphyrin [9,14], cobalt porphine [15] and free base tetraphenylporphyrin [16] and electrodeposited platinum particles [8], on the oxygen reduction by DMFc at the water/DCE interface has also been investigated. Moreover, it has been found very recently that under anaerobic conditions DMFc could also reduce aqueous proton to produce hydrogen at the water/DCE interface [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that oxygen and proton could be reduced to hydrogen peroxide and hydrogen by the strong electron donor decamethylferrocene (DMFc) at the water/1,2-dichloroethane (DCE) interface under aerobic and anaerobic conditions, respectively. 2,3 In the case of oxygen reduction, the catalytic effect of in situ generated interfacial Pt nanoparticles 6 and that of different metalated 4,5,8,9 and freebase porphyrins 7,10 have also been demonstrated, showing that both adsorbed Pt particles and porphyrins can act as oxygen binding sites.…”
mentioning
confidence: 99%